Exploring purposes of using taxonomies - Schoormann, T.; Möller, F.; Szopinski, Daniel (Tagungsband der 17. Internationalen Tagung Wirtschaftsinformatik 2022)

Kultur – Daten – Kuratierung: Was Speichern Wir Und Wozu? - Altenhöner, Reinhard; Dieckmann, Lisa; Münzmay, Andreas; Richts-Matthaei, Kristina; Röwenstrunk, Daniel; Stellmacher, Martha; Pratschke, Margarete; Primavesi, Patrick; Schulz, Christoph

Visual Interpretability of Image-based Real Estate Appraisal - Kucklick, Jan-Peter (55th Annual Hawaii International Conference on System Sciences (HICSS-55))
Explainability for machine learning gets more and more important in high-stakes decisions like real estate appraisal. While traditional hedonic house pricing models are fed with hard information based on housing attributes, recently also soft information has been incorporated to increase the predictive performance. This soft information can be extracted from image data by complex models like Convolutional Neural Networks (CNNs). However, these are intransparent which excludes their use for high-stakes financial decisions. To overcome this limitation, we examine if a two-stage modeling approach can provide explainability. We combine visual interpretability by Regression Activation Maps (RAM) for the CNN and a linear regression for the overall prediction. Our experiments are based on 62.000 family homes in Philadelphia and the results indicate that the CNN learns aspects related to vegetation and quality aspects of the house from exterior images, improving the predictive accuracy of real estate appraisal by up to 5.4%.
Keywords: Explainable Artificial Intelligence (XAI); Regression Activation Maps; Real Estate Appraisal; Convolutional Block Attention Module; Computer Vision

Using Geolocated Text to Quantify Location in Real Estate Appraisal - Heuwinkel, Tim; Kucklick, Jan-Peter; Müller, Oliver (55th Annual Hawaii International Conference on System Sciences (HICSS-55))
Accurate real estate appraisal is essential in decision making processes of financial institutions, governments, and trending real estate platforms like Zillow. One of the most important factors of a property’s value is its location. However, creating accurate quantifications of location remains a challenge. While traditional approaches rely on Geographical Information Systems (GIS), recently unstructured data in form of images was incorporated in the appraisal process, but text data remains an untapped reservoir. Our study shows that using text data in form of geolocated Wikipedia articles can increase predictive performance over traditional GIS-based methods by 8.2% in spatial out-of-sample validation. A framework to automatically extract geographically weighted vector representations for text is established and used alongside traditional structural housing features to make predictions and to uncover local patterns on sale price for real estate transactions between 2015 and 2020 in Allegheny County, Pennsylvania.
Keywords: Real Estate Appraisal; Text Regression; Natural Language Processing (NLP); Location Intelligence; Wikipedia

Electric-field-induced second harmonic generation in silicon dioxide - Widhalm, Alex; Golla, Christian; Weber, Nils; Mackwitz, Peter; Zrenner, Artur; Meier, Cedrik (Optics Express)
Keywords: Atomic and Molecular Physics; and Optics

Low-Power Low-Data-Rate Wireless PPM Receiver Based on 13-Bits Barker Coded SAW Correlator with Scalable Data-Rate and Sensitivity - Abughannam, Saed; Scheytt, J. Christoph (International Symposium on Circuits and Systems (ISCAS 2022))

Fachliche und überfachliche Herausforderungen in der Studieneingangsphase Physik - Bauer, Anna; Woitkowski, David; Reuter, Dirk; Reinhold, Peter (Hochschullehre erforschen.)
Die Studieneingangsphase Physik stellt für die Studienanfänger Innen einen komplexen Lernprozess mit vielfältigen Anforderungen auf fachlicher, Metakognitions- und Sozialisations-Ebene dar, der ihre akademische Identitätsbildung beeinflusst und prägt. Ziel des Projektes Paderborner Studieneingangsphase Physik (PSΦ) ist die evidenzbasierte Gestaltung eines strukturierten Studieneinstiegs und einer in sich kohärent abgestimmten Studieneingangsphase „aus einem Guss“. Die Implementation eines neuen Übungsformats (Präsenzübungen) in den Fachvorlesungen sowie die Unterstützung der Studierenden im Bereich des selbstregulierten Lernens zeigen positive Effekte in einer erhöhten Teilnahmequote sowie Zufriedenheit der Studierenden mit der Veranstaltung, in einem aktiveren Arbeitsverhalten sowie einer höheren Bestehensquote der Klausur. Ein messbar größerer Fachwissenserwerb konnte nicht nachgewiesen werden. Auf Basis der Evidenzen konnten Stellschrauben für die Weiterentwicklung sowie für die Unterstützung der Lehrenden abgeleitet werden. In dem Beitrag werden die Gelingensbedingungen und Strukturen für eine wirksame Zusammenarbeit von Fachdidaktik und Fachwissenschaft am Beispiel der Überarbeitung der Studieneingangsphase im Rahmen einer community of practice sowie der Wirksamkeit der Implementierung diskutiert.

Capacity investments in a competitive energy market - Block, Lukas; Westbrock, Bastian
We study the abilities of competitive markets to produce sufficient energy capacities to meet a fixed energy demand. Renewable energy producers with stochastic outputs and no variable costs compete against conventional energy producers with deterministic, pollutant outputs and increasing marginal costs. We find that either market forces are strong enough to serve the entire demand, or they are too weak such that the market fails and nothing is produced. This crucially depends on the relative cost of renewable energy investments, such that relatively cheap renewable energy causes the market to fail. Welfare analyses show that with increasing levels of conventional energy pollution the ability of the market to produce an ecient outcome further declines. As a policy implication, our findings refute the use of a strategic reserve as a blackout backstop solution. Instead, a capacity mechanism consisting of a tax-and-subsidy scheme can align the market outcome with the eficient solution for all pollution levels and relative costs of renewable energy capacities.
Keywords: Renewable versus conventional energy; capacity mechanisms; strategic reserves; capacity payments

Designing a GIS-AHP-Based Spatial Decision Support System for Discovering and Visualizing Suitable Locations for Electric Vehicle Charging Stations - Priefer, Jennifer; Steiger, Lennart (Wirtschaftsinformatik 2022 Proceedings)

Influence of thermomechanical processing on the microstructural and mechanical properties of steel 22MnB5 - Reitz, A.; Grydin, O.; Schaper, M. (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Situational Business Model Developer: A Tool-support for Situation-speciﬁc Business Model Development - Gottschalk, Sebastian; Yigitbas, Enes; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
The development of business models is a challenging task that can be supported with software tools. Here, existing approaches and tools do not focus on the company’s situation in which the development takes place (e.g., ﬁnancial resources, product type). To tackle this challenge, we used design science research to develop a situation-speciﬁc business model development approach that contains three stages: First, existing knowledge in terms of tasks to do (e.g., analyze competitive advantage), and decisions to be made (e.g., social media marketing) are stored in repositories. Second, the knowledge is used to compose a development method based on the company’s situation. Third, the development method is enacted to develop a business model. This demonstration paper presents a tool-support called Situational Business Model Developer that supports all stages of our approach. We release the tool under open-source and evaluate it with a case study on developing business models for mobile apps.
Keywords: Business Model Development; Situational Method Engineering; Tool Support

Development and Evaluation of a Collaborative Stock Trading Environment in Virtual Reality - Yigitbas, Enes; Gottschalk, Sebastian; Nowosad, Alexander; Engels, Gregor (Proceedings of the 17th International Conference on Wirtschaftsinformatik)
Due to the proliferation of Virtual Reality (VR) technology, VR is finding new applications in various domains, such as stock trading. Here, traders invest in stocks intending to increase their profit. For this purpose, in conventional stock trading, traders usually make use of 2D applications on desktop or laptop devices. This leads to many drawbacks such as poor visibility due to limited 2D representation, complex interaction due to indirect interaction via mouse and keyboard, or restricted support for collaboration between traders. To overcome these issues, we have developed a novel collaborative, virtual environment for stock trading, which enables stock traders to view financial information and trade stocks with other collaborators. The main results of a usability study indicate that the VR environment, compared to conventional stock trading, shows no significant advantages concerning efficiency and effectiveness, however, we could observe an increased user satisfaction and better collaboration.
Keywords: virtual reality; stock trading; collaboration; usability

A Discrete and Continuous Study of the Max-Chain-Formation Problem - Castenow, Jannik; Kling, Peter; Knollmann, Till; Meyer auf der Heide, Friedhelm (Information and Computation)
Keywords: Computational Theory and Mathematics; Computer Science Applications; Information Systems; Theoretical Computer Science

Semi-automatic Integrated Safety and Security Analysis for Automotive Systems - Fockel, Markus; Schubert, David; Trentinaglia, Roman; Schulz, Hannes; Kirmair, Wolfgang (Proceedings of the 10th International Conference on Model-Driven Engineering and Software Development)

Integrating Security Protocols in Scenario-based Requirements Specifications - Koch, Thorsten; Trippel, Sascha; Dziwok, Stefan; Bodden, Eric (Proceedings of the 10th International Conference on Model-Driven Engineering and Software Development)

Kompetenzentwicklung im inklusiven Unterricht (KinU) – eine internationale Perspektive - Albers, Timm; Filipiak, Agnes; Franzen, Katja; Hellmich, Frank (Grenzen.Gänge.Zwischen.Welten. Kontroversen – Entwicklungen – Perspektiven der Inklusionsforschung)

Methodenentwicklung zur Versagensanalyse aufgrund der Aushärtung vorgeschädigter Klebverbindungen in stahlintensiven Mischbaustrukturen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson; Aubel, Tobias; Matzenmiller, Anton (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Lebensdauerprognose für Stahlklebverbindungen bei multiaxialer Belastung mit Phasenverschiebung, veränderlicher Mittelspannung und variablen Amplituden - Carillo Beber, Vinicius; Nagel, Christof; Mayer, Bernd; Köster, Christian; Matzenmiller, Anton; Hecht, Matthias; Baumgartner, Jörg; Melz, Tobias; Tews, Karina; Çavdar, Serkan; Meschut, Gerson (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)

Funnel control of linear systems under output measurement losses - Lanza, Lukas Johannes; Berger, Thomas

Network and Service Coordination: Conventional and Machine Learning Approaches" - Schneider, Stefan Balthasar